THE EFFECT OF CONSUMER BEHAVIOR STUDENTS UNIVERSITY STATE OF JAKARTA ON PRODUCT ONLINE PURCHASE’S DECISION ON ONLINE SHOP BUKALAPAK.COM - Adi, Wasono (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
The development of the Internet technology becomes the precursor of the progress of business over the Internet that is significantly growing up in the recent year. In the present, people like to shop through online shops, because in addition to its practicality, the price of goods offered is relatively affordable, and, or relatively equal to conventional stores. One of the online stores which are popular amongst Indonesian society, and also popular for the university student in Indonesia is Buka Lapak.com. This research aims to examine the influence of consumer behavior on their buying decisions (studies on consumer of Buka Lapak.com amongst the student of Universitas Negeri Jakarta ). The method used in this research is quantitative method with simple linear regression analysis. The results show that student’s consumer behavior in today’s technology significantly influences the student’s buying decisions on Buka Lapak.com. This is shown by the correlation coefficient test result, in which the level of relationship between the student’s consumers behavior toward buying decisions on Buka Lapak.com is included in the category of strong and direct.